Regional Economic Impacts of Immigration: A Review - Simonetta Longhi; Peter Nijkamp; Jacques Poot (Tinbergen Institute, 2009)
A burgeoning literature has emerged during the last two decades to assess the economic impacts of immigration on host countries. In recent years much research has been at the national level under the assumption that impacts in open regions may dissipate through adjustment processes such as factor mobility. However, this is ultimately an empirical issue. In this paper we revisit the impacts of immigration at the regional level. We briefly review analytical approaches for identifying regional economic impacts, specifically the labour market impact. A meta-analytic approach is adopted. As a novel contribution to existing meta-analyses on labour market impacts, we use a simultaneous equations approach to the meta-analysis of wage and employment effects. The number of studies that informs on both effects is rather limited, but eight econometric analyses yielded 130 useful meta-observations. We find that wage rigidity increases the magnitude of the employment impact on the native born, particularly of those who are low skilled, following positive net immigration. The employment elasticity is also greater in Europe than in the United States. However, observed employment elasticities are not informative about whether larger or smaller wage effects may be expected.
Keywords: F22; J61; R23; 330; international migration; regional labour market; meta-analysis; impact analysis; regional growth; Internationale Wanderung; Beschäftigungseffekt; Regionaler Arbeitsmarkt; Makroökonomischer Einfluss; Regionale Entwicklung; Meta-Analyse; Schätzung; EU-Staaten; USA